Antioxidant and Anti-Inflammatory Activities of Biofield Energy Treated Proprietary Test Formulation in Brain Tissues in Cecal Slurry, LPS and E. Coli-Induced Systemic Inflammatory Response Syndrome (SIRS) in Sprague Dawley Rats - Mahendra, Kumar Trivedi; Alice, Branton; Dahryn, Trivedi; Snehasis, Jana (International Journal of Global Health, 2021)
LPS and E. Coli-Induced SIRS in Sprague Dawley Rats